Thermoelectrically controlled micronozzle - A novel application for thermoelements - Hameed, Amar Hasan; Kafafy, Raed (Springer, 2012)
This paper introduces and assesses the concept of the recently invented thermoelectrically controlled micronozzle (TECMN). A generalized quasi-one-dimensional model for gas flow, which is influenced by area variation and by wall heat transfer, is considered. In order to assess the merits of wall temperature control in micronozzles, the flow in the micronozzle is solved numerically for cases of convergent wall heating, divergent wall cooling, and a combination of both. Thermal efficiency and specific impulse are affected by heat exchange through the side wall of the micronozzle. By cooling the divergent section, kinetic energy increases, thus improving thermal efficiency. The mass flow rate is decreased in all cases that include convergent section heating, thereby enhancing specific impulse. The combination of convergent section heating with divergent part cooling results in significant performance enhancement in terms of thermal efficiency and specific impulse. To determine the TECMN wall temperature profile, we developed a one-dimensional general energy model for a thermoelement (TE) subject to an electric field as well as for heat convection on the lateral surface. The energy equation is analytically solved for constant properties and for Joule heating equivalent to heat convection. The temperature profile is then imposed on the quasi-one-dimensional flow model, which is solved numerically for various mass flow rates and exit wall temperature (cold junction). As the exit section wall temperature and mass flow rate decrease, the utilization of TEs to control the temperature of micronozzle walls considerably increases the Mach number at exit.